New insights on the geographical origins of the Caribbean raccoons. (24th April 2020) - Louppe, Vivien; Baron, Juliette; Pons, Jean‐Marc; Veron, Géraldine
Abstract: The introduction of species outside their natural range is one of the major threats to biodiversity and has often been identified as a menace to agricultural production and human health. The raccoon is recognized as a globally invasive species. However, several populations in the Caribbean were long considered native and endemic species. Although previous genetic studies have shown that raccoons from the islands of the West Indies belong to the northern raccoon Procyon lotor, the history and origin of these introductions remain poorly known. In this study, we investigated the geographical origin of Caribbean raccoon populations using newly available molecular genetic data. We used haplotype network analyses of two mitochondrial markers, Cytochrome b and Control Region, with new sequences and those from GenBank. We also specifically investigated the origin of the endangered endemic Cozumel raccoon, Procyon pygmaeus, by re‐analyzing data. Our results confirmed that all Caribbean raccoon populations belong to the northern raccoon. Bahamian populations originated from two different sources in Florida, and the Lesser Antilles raccoons seem to originate from northern regions of the native range. In addition, our results question the taxonomic status of the Cozumel raccoon, as currently available genetic data support a conspecific status with the northern raccoon. These results have important implications in the context of conservation and ecosystem management. Identifying origins of introduced populations and understanding the history of their introductions will facilitate studies on the impact of the raccoon on insular ecosystems. Abstract : The raccoon is recognized as a globally invasive species. However, several populations in the Caribbean were long considered native and endemic species. In this study, we investigated the geographical origin of Caribbean raccoon populations using newly available molecular genetic data. Our results confirmed that all Caribbean raccoon populations belong to the northern raccoon. In addition, our results question the taxonomic status of the Cozumel raccoon, as currently available genetic data support a conspecific status with the northern raccoon.